Unlearning Traditionalism: The Long-Run Effects of Schools on Gender Attitudes - Javier Garcia-Brazales (ZBW - Leibniz Information Centre for Economics, 2022)
Can sustained exposure to females persistently modernize gender attitudes? I study the impact of female peers and teachers on gender roles, perceived relative gender ability, and gender-related behaviors up to nine years later. For this, I exploit two-decade longitudinal information on cognition, attitudes, aspirations, and expectations of a close-to-nationally-representative cohort of Vietnamese primary schoolers exogenously allocated to peers and teachers. I find evidence that being exposed to a higher proportion of female peers weakens traditional gender views both for males and females, and that this translates into actual behavior. Females increase their probability of enrolling at university and in male-dominated majors. A decomposition exercise shows that this is mainly mediated by increased academic aspirations, higher expected returns to education, and less traditional views on the acceptable life goals for females. Males increase both the intensive and extensive margins of home production. These results suggest that early exposure to females can shift slow-moving attitudes even in contexts of high overall cross-gender interactions.
Keywords: I24; I25; J16; 330; Gender Norms; Attitude Formation; Contact Theory; Long-term Peer Effects; Returns to Education